To solve the system of equations:
- \( 3x + y = 2 \) (Equation 1)
- \( 7x - 4y = 30 \) (Equation 2)
We can use the substitution or elimination method. Let's use substitution.
From Equation 1, we can express \( y \) in terms of \( x \):
\[ y = 2 - 3x \]
Now, substitute \( y \) into Equation 2:
\[ 7x - 4(2 - 3x) = 30 \]
Distributing the \(-4\):
\[ 7x - 8 + 12x = 30 \]
Combining like terms:
\[ 19x - 8 = 30 \]
Adding 8 to both sides:
\[ 19x = 38 \]
Dividing by 19:
\[ x = 2 \]
Now, substitute \( x = 2 \) back into the equation for \( y \):
\[ y = 2 - 3(2) = 2 - 6 = -4 \]
Thus, the solution to the system of equations is:
\[ (x, y) = (2, -4) \]
So the answer is:
(2, -4)